Professional Linguistic Personality of A Philologist: Content and Semantic Analysis of M.M. Bakhtin's Texts - Bektursinova Aysultan Marat qizi (Peerian Journals Publishing, 2023)
In the light of the ever-growing interest in the anthropocentric paradigm, topical issues in linguistics today are the issues of studying the professional linguistic personality of a scientist. In this article, we consider the content and semantic side of M.M. Bakhtin's text array, the analysis of which will allow us to contribute to a number of scientific studies devoted to determining the type of professional linguistic personality of a philologist.
Keywords: Bakhtin; idiodiscourse; linvoritoric paradigm; text